Evaluation of the durability and ageing of false banana fiber in different chemical environments - Addis, Lulseged Belay; Sendekie, Zenamarkos Bantie; Habtu, Nigus Gabbiye; Roether, Judith; Schubert, Dirk W.; Boccaccini, Aldo R. (Industrial Crops and Products, 2025)
This study explores the effect of three types of ageing conditions on the structural, chemical, and morphological properties of fibers extracted from the false banana (Ensete ventricosum) plant: distilled water, 5 % sodium sulphate solution, and sulfuric acid solutions of varying concentrations (0.5 %, 1 %, and 2 %). The main objective is to assess the fibers’ stability and durability after prolonged exposure to various chemical conditions, which simulate future service environments and have implications for their use in natural fiber-reinforced geopolymer composites. To achieve this, a comprehensive set of analyses was performed to investigate changes in the fiber’s chemical structure, surface morphology, single fiber tensile strength, thermal degradation behavior, and crystallinity index before and after six months of ageing induced by each type of treatment. The results showed that distilled water and a 5 % sodium sulphate solution had little influence on the fibers’ structural integrity and physical properties after six months of exposure when compared to the fibers as-received. However, exposure to sulfuric acid at higher concentrations has had a deleterious effect on fiber strength, severe surface erosion, a change in functional groups as detected by FTIR analysis, and a significant reduction in fiber crystallinity index values. Furthermore, a contour map was created using the crystallinity index value, and an interesting correlation was discovered between the crystallinity index and the product of exposure time and acid concentration. Thus, the test results provide a fundamental understanding of some of the most important changes in false banana plant fiber properties caused by ageing, indicating their potential use in sustainable construction materials where chemical resistance is critica
Keywords: Contour plot; Crystallinity index; Fiber degradation; Fiber tensile strength; Law of superposition